Innovative fisheries extension methodology —its impact on fisheries development in Karnal - Markanday, Jagdish (Indian Farming, 2015)
In the state of Haryana, there was a time when large number of ponds furnished by rainwater lay unutilized. An innovative extension methodology used by the scientists in the Karnal district for fish farming, could convince the village Panchayats and the local people to take up fish farming to earn a good profit by selling these fishes. A training imparted by the scientists to the unemployed local youths could bring a change in their attitude towards fish farming.